Perturbation Method for a Parabolic Equation with Drift on a Riemannian Manifold - Bernatskaya, J. N. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We construct a fundamental solution of a parabolic equation with drift on a Riemannian manifold of nonpositive curvature by the perturbation method on the basis of a solution of an equation without drift. We establish conditions for the drift field under which this method is applicable.